Systematic Review of Health Emergency Policies and Their Impact on Referral Mechanisms During the COVID-19 Pandemic - Naufal Ivanda, Rio Revaldi; Salma, Dewi; Joanna, Adila Helga; Sava Athadita, Anindya Fathin; Saputri, Puput; Cellia, Natasya Nawa; Syahida, Bilqis Ayu; Handartiwi, Refiana Martha; Ghozi Abdullah, Muhammad Nur Hakim; Ningrum, Titah Wahyu; Santi, Neni Fidya; Evi, Nurul (Tarqabin Nusantara Group, 2025)
The COVID-19 pandemic placed unprecedented strain on healthcare systems worldwide, necessitating rapid policy interventions to manage patient flow, resource allocation, and referral mechanisms. This study employed a systematic literature review (SLR) using the PRISMA framework to evaluate the impact of health emergency policies on referral mechanisms during the pandemic. The review focused on understanding how policies such as lockdowns, triage protocols, and telemedicine integration influenced access, equity, system efficiency, and resilience in referral networks. A comprehensive search was conducted across databases including PubMed, Scopus, Web of Science, IEEE Xplore, and Cochrane Library, with inclusion criteria encompassing peer-reviewed studies published in English between 2020 and 2023. Studies were rigorously assessed for methodological quality using tools such as the Cochrane Risk of Bias Tool and Simulation Model Quality Assessment Framework. Key themes identified included restricted access to emergency services, healthcare system reordering, operational strain on infrastructure, and coordination gaps. The findings revealed significant challenges, such as ambulance delays, emergency department closures, protocol overload, and inequities in care access, while also highlighting adaptive strategies like AI-driven referral tools, hybrid triage systems, and community health worker networks. This study underscores the need for balanced policy design, robust technological integration, and long-term systemic reforms to strengthen referral mechanisms during health emergencies. The results provide actionable insights for policymakers and healthcare administrators to optimize referral systems and ensure equitable access to care during future crises.